Professional development of educators : an illuminative evaluation of INSET for life orientation. - Shah, Zahira (My University, 2012)
In-service education and training (INSET) has become a key vehicle for the professional development of educators in the school context. However, its role and impact has yet to be fully comprehended. This study resulted from the realization that educators often attend short training courses without being tracked or monitored afterwards. Using an illuminative approach to evaluation, this study aimed to establish the impact of INSET on educators’ ability to effectively implement the Life Orientation (LO) curriculum, after attending national INSET in 2005. It was also important to gauge if educators had gained the knowledge and skills to deal with emergent issues not addressed during the training. The field of adult education offered a particular lens through which I aimed to look at both LO and INSET. The sample selected for this study consisted of three teachers teaching at co-educational government schools in Johannesburg, who attended the 2005 Gauteng provincial training in LO for grade 10. Data collection methods included questionnaires, naturalistic observations, semi-structured interviews and document analysis. The findings of this study suggest that the success of this INSET programme depends heavily on the individuals who attend them and their personal experiences and beliefs. The study concluded that for educators to implement LO effectively they would not only have to develop professionally but they should also be committed to lifelong learning.
Keywords: In-service education and training; Life orientation; National Curriculum Statement; Professional development; South Africa